Socio-economic status of dragon fruit farmers in Haryana (IASH Indian Journal of Arid Horticulture, 2026)
The study was undertaken to analyse the socio-economic status of dragon fruit farmers from all over Haryana. The results revealed that the majority of dragon fruit growers (58.75%) belonged to the middle-age group of 35–50 years, indicating active working participation. In terms of education, 42.5% growers attained senior secondary level, while 25% were graduates and above, reflecting relatively better literacy compared to the general farming community. About 70% of the respondents belonged to nuclear families. The small and medium farmers dominated with 26.25% and 27.5% share, respectively, while only 5% were large farmers. Annual income ranged mostly between ₹ 1.5–3.0 lakh (57.5%). Nearly half of the farmers (48.75%) cultivated dragon fruit on one acre, while 27.5% had less than one acre under the crop.